Hepatitis A Person-to-Person Outbreaks: Epidemiology, Morbidity Burden, and Factors Associated With Hospitalization—Multiple States, 2016–2019. (24th October 2020) - Hofmeister, Megan G; Xing, Jian; Foster, Monique A; Augustine, Ryan J; Burkholder, Cole; Collins, Jim; McBee, Shannon; Thomasson, Erica D; Thoroughman, Douglas; Weng, Mark K; Spradling, Philip R
Abstract: Background: Since 2016, the United States has experienced person-to-person hepatitis A outbreaks unprecedented in the vaccine era. The proportion of cases hospitalized in these outbreaks exceeds historical national surveillance data. Methods: We described the epidemiology, characterized the reported increased morbidity, and identified factors associated with hospitalization during the outbreaks by reviewing a 10% random sample of outbreak-associated hepatitis A cases in Kentucky, Michigan, and West Virginia—3 heavily affected states. We calculated descriptive statistics and conducted age-adjusted log-binomial regression analyses to identify factors associated with hospitalization. Results: Participants in the random sample (n = 817) were primarily male (62.5%) with mean age of 39.0 years; 51.8% were hospitalized. Among those with available information, 73.2% reported drug use, 14.0% were experiencing homelessness, 29.7% were currently or recently incarcerated, and 61.6% were epidemiologically linked to a known outbreak-associated case. Residence in Michigan (adjusted risk ratio [aRR] = 1.8), being a man who has sex with men (aRR = 1.5), noninjection drug use (aRR = 1.3), and homelessness (aRR = 1.3) were significantly ( P  < .05) associated with hepatitis A-related hospitalization. Conclusions: Our findings support current Advisory Committee on Immunization Practices recommendations to vaccinate all persons who use drugs, men who have sex with men, and persons experiencing homelessness against hepatitis A. Abstract : This report describes the epidemiology of person-to-person hepatitis A outbreaks, characterizes the morbidity burden, and identifies factors associated with hospitalization (state of residence, noninjection drug use, being a man who has sex with men, and homelessness) during the outbreaks.